On the relationship between religious fundamentalism and political fundamentalism in Polish reality = O związkach fundamentalizmu religijnegoz fundamentalizmem politycznym w warunkach polskich - Jeliński, Edward (Przegla̜d religioznawczy, 2020)
The subject of the author’s interest is the problem of the relationship between religious fundamentalism and political fundamentalism. The author starts with the adopted doctrinal and theoretical findings to proceed to the analysis of selected practical solutions related to Polish socio-political reality in recent times. The attention is focused on the issues of the relations between the state and the Catholic Church in Poland. He concludes his considerations with a message (very current) from J. Turowicz about the Catholics’ responsibility for the implementation and observance of ethical standards in social and political life.